Hardness Evaluation on SS 316L Joined with Gas Tungsten Arc Welding Under Constant Heat Treatment - Edy, Duwi Leksono; Sujono, Imam (Journal of Mechanical Engineering Science and Technology (JMEST), 2020)
The purpose of this study is to show the hardness of the GTAW welding results on SS 316L metal with surface heating during the welding process. Observations in this study used SS 316L material with heat temperature regulation on the metal surface of the welding process using heating variations of 100 ℃, 120 ℃ and 140 ℃. The welding process of SS 316L material used a welding joint model uses single V-type welding joint with an angle of 60°, a spacing of 2 mm, a root surface of 1 mm and a thickness of 5 mm. Vickers hardness test was conducted to evaluate the hardness of samples. The results indicate that all specimens show a difference in the level of violence comparing with the values of the average level of hardness in each weld specimen. Specimens with the welding process heating temperature 100 ℃ have an average hardness value of 115.6 HVN. In contrast, samples with heating 120 ℃ have increased by having an average hardness value of 131.0 HVN. In comparison, heating specimens with heating surfaces of welding 140 ℃ have an increase in hardness values with an average of 171.5 HVN.